Proceedings from the National Symposium on Makhana: Unlocking India’s aquatic superfood for rural prosperity - Pahwa, Vanshika; Sirsikar, Ishita; Singh, Ritambhara; Shukla, Navneet Prabhakar; Verma, Kannan Kumar; Sachdev, Avinash (International Food Policy Research Institute, 2025)
Makhana, also known as gorgon nut, is a nutrient-rich aquatic crop that is primarily cultivated in India, with northern Bihar being the major production region. With a cultivation history of over 2,000 years, makhana is recognized for its nutritional profile, which includes approximately 76.9% carbohydrates, 9.7% protein, and essential minerals. More than 85% of India’s makhana is produced in the districts of Darbhanga, Madhubani, Purnia, and Katihar in Bihar, covering an estimated 15,000 hectares. The annual production of makhana is around 120,000 metric tons (MT) of seeds, resulting in 40,000–50,000 MT of popped makhana. The sector is expected to generate revenues of approximately ₹600 crore at the trader level. However, exports are limited, with roughly 1% of the production reaching international markets such as the USA, UK, Australia, and Gulf countries. In 2022, the Government of India registered ‘Mithila Makhana’ as a Geographical Indication (GI), recognizing its regional and product-specific characteristics. Under the One District One Product (ODOP) scheme, six makhana-producing districts in Bihar have been selected for focused development. Additionally, the Union Budget 2025 announced the creation of a dedicated Makhana Board in Bihar to support the sector across various stages, including production, processing, value addition, and market access. The domestic market for makhana is projected to reach ₹18.9 billion by 20322, indicating potential for further growth and development in the sector.